Antisaccadic eye movements in middle-aged individuals with a family history of Alzheimer's disease - Peng, Anjiao; Lai, Wanlin; Liu, Zhu; Wang, Mingda; Chen, Shujuan; Zhao, Xia; Zhu, Yuanfeng; Chen, Lei (Frontiers in Human Neuroscience, 2023)
Background Antisaccade is closely associated with cognitive ability in Alzheimer's disease (AD). However, studies regarding antisaccade in the early stages of AD are scarce. Considering that first-degree family history is a well-established risk factor for AD, we explored the influence of family history on the performance of antisaccade tasks in individuals with normal cognition. Methods In total, 44 participants (aged 50–66 years) with a family history of AD (FH+) and 44 age-, gender-, and educational level-matched controls (FH-) were enrolled in our study. After cognitive assessment using the Montreal Cognitive Assessment and Mini-mental State Examination, participants underwent antisaccade trials, and all parameters were recorded using an eye tracker. Results While the average velocity was relatively lower in FH+ individuals than in FH− individuals (107.9 ± 14.3°/s vs. 132.9 ± 23.7°/s, p < 0.001), FH+ individuals surprisingly showed relatively fewer uninhibited reflexive saccades (44.7 ± 26.0% vs. 56.2 ± 24.7%, p = 0.037) than the control group. They also required a relatively shorter time to detect and correct false saccades (121.6 ± 40.7 ms vs. 143.9 ± 37.0 ms, p = 0.023). Conclusions This study showed that family history is associated with alterations in antisaccadic parameters, suggesting that eye tracking can be used to assess oculomotor control and executive function in individuals at risk of developing dementia.